El enigma de la parte central del Ms. Aubin No 20 y la relación con sus copias - Katarzyna Mikulska (Journal de la Société des Américanistes)
The central part of the Manuscrito Aubin No. 20 (BNF, Ms. Mexicain 20), housed in the Bibliothèque nationale de France (BNF) as part of the Mexican Collection, has disappeared. It is widely believed that two copies of this codex that were undertaken in the 18th century managed to reproduce the central part of this document before its erasure. This view does not seem to have been questioned, apart from a doubt expressed by Maarten Jansen some time ago. Therefore, when a reproduction of Ms. 20 is needed in any publication, it is frequently accompanied by the reproduction of the copy made by León y Gama (BNF, Ms. Mexicain 21) so as to supply the missing image. On the basis of codicological research, the aim of this article is to verify if the copy by León y Gama, and the one made by Father Pichardo (BNF, Ms. Mexicain 88-4), can be treated as reliable reproductions The codicological study of the original document will also allow the formulation of a hypothesis regarding the possible use of the original indigenous document.